Distribution pattern of rare earth elements in soft tissue of saccostrea cucullata in Terengganu and East Johor coastal waters - Mat Ali, Siti Nabila; Kammoo, Muhammad Farhan; Nik Ali, Nik Nurizni; Miskon, Mohd Fuad (Zibline International Publisher, 2019)
This study determined the concentration and accumulation pattern of REEs in the soft tissue of Saccostrea cucullata with respect to interspatial variability. Variability in the concentration of REEs in soft tissue of S. cucullata was observed in all samples with significant differences among samples associated with sampling sites (p < 0.05). The distribution pattern of REEs’ concentration in soft tissue of S. cucullata is uniformly distributed among sampling sites with enrichment of light REE, LREE over heavy REE, HREE. The same accumulation pattern indicate that REEs are transported as a coherent group in aquatic ecosystem. All REEs yielded positive correlation among each elements in the soft tissue of S. cucullata. Average distribution of REEs in soft tissue of S. cucullata indicated that East Johor has the most abundance of REEs’ concentration compared to Terengganu coastal water. This occurrence probably due to higher urbanization and industrialization activities such as sewage and effluent wastes. ST10 located in East Johor region has the most abundance of REEs while ST4 located in Terengganu region has the lowest concentration of REEs with Ce as the most abundance element and Dy as the least abundance element. The distribution pattern of REEs’ concentration in this study is slightly different. There is significant differences between concentration of all REEs in the soft tissue of S. cucullata in the year of 2013 and 2017 except for La, Ce and Nd (p < 0.05).